Hypertension in Relation with Smoking in Azadi Teaching Hospital at Kirkuk City - Saad S. Mustafa1, Taghlub H. Ryhan2, Ali A. Ismail3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: smoking and hypertension are two common health problems effecting body organs and increasing morbidity and mortality.Aim of Study: determining the relationship between smoking and hypertension, the affect of the amount and duration of smoking on the severity of hypertension and complications of smoking among hypertensive patient.Patient and Method: the study is cross sectional, in which 200 hypertensive patient were collected in Azadi Teaching Hospital in Kirkuk. There blood pressure was measured and the patients were asked about smoking habits, and if they have complication of hypertension.Results: hypertension is more common among male, married, illiterate and primary educated, intermediate socioeconomic state, physically inactive and more in urban than rural area. Uncontrolled rate of hypertension is high in both smokers and non smokers and this rate increase with increase with increasing duration of smoking. Heart and cerebrovascular complications of hypertension is very high in smokers compared with non smokers. P-value less than 0.05 regard as significant relationship.Conclusion: very low control rate of hypertension in both smokers and non smokers. We recommended public health education via mass media regarding the side effect of smoking combined with hypertension and it’s complications.